Emergency Providers' Familiarity with Firearms: A National Survey. (20th January 2020) - Ketterer, Andrew R.; Poland, Scott; Ray, Kaitlin; Abuhasira, Ran; Aldeen, Amer Z.
Abstract: Background: Emergency providers (EPs) are uniquely placed to advocate for firearm safety and have been shown to be at risk of exposure to firearms in the emergency department (ED). We sought to characterize EPs' knowledge of firearms, frequency of encountering firearms in the ED and level of confidence with safely removing firearms from patient care settings. Methods: This was a survey study of EPs representing medical centers in 22 states. A 15‐item questionnaire was e‐mailed to all EPs at all included institutions. Questions pertained to EPs' knowledge of firearms, experience with handling firearms, and exposure to firearms while at work. We calculated response proportions with p‐values and conducted association analyses among survey items. Results: Of 2, 192 survey recipients, 1, 074 (49.0%) completed the survey. A total of 635 (59.1%) reported encountering firearms in the ED or its immediate environment at least once per year, and 582 (54.2%) were not confident in their ability to safely handle a firearm found in a patient's possession. Frequency of handling firearms was significantly higher in states in the top quartile for firearm ownership, with 21.5% of respondents reporting handling firearms daily or weekly, compared to 10.9% in bottom‐quartile states. Level of firearms training also differed significantly: 42.1% of respondents in top‐quartile states reported formal training compared to 33.0% in bottom‐quartile states. Increased regional firearm ownership rates were associated with decreased rates of feeling unsafe at work. Conclusions: The majority of surveyed EPs reported little experience with handling firearms. Firearm experience was associated with comfort with managing firearms found in patients' possession. Regional differences were found regarding personal firearm experience and perceptions of workplace safety, both of which were associated with regional variations in firearm ownership. Despite this, no regional differences were found in encountering firearms in or around the ED. EPs may benefit from training on safely handling firearms.